2009
DOI: 10.1016/j.jcrs.2009.04.032
|View full text |Cite
|
Sign up to set email alerts
|

Combined cataract extraction and intravitreal bevacizumab in eyes with choroidal neovascularization resulting from age-related macular degeneration

Abstract: Combined phacoemulsification, IOL implantation, and intravitreal bevacizumab was a safe and efficacious treatment in patients with visually significant cataract and active subfoveal neovascularization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
22
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 36 publications
5
22
0
Order By: Relevance
“…We did not study cataract surgery with simultaneous bevacizumab injection in patients with active exudative AMD as Furino et al 10 Even though, this study reported visual gains at one month, the long-term results of this approach are unknown.…”
Section: -11mentioning
confidence: 94%
See 4 more Smart Citations
“…We did not study cataract surgery with simultaneous bevacizumab injection in patients with active exudative AMD as Furino et al 10 Even though, this study reported visual gains at one month, the long-term results of this approach are unknown.…”
Section: -11mentioning
confidence: 94%
“…The data presented included visual acuity results up to four months after the surgery and there is no reference to the percentage of patients that gained or lost vision. Furino et al 10 showed favorable results one month after combined phacoemulsification and bevacizumab in an active exudative AMD setting. Tabandeh et al 11 reported similar visual acuity gains in a follow-up period that was shorter than twelve months, in patients that had phacoemulsification whilst being treated with either ranibizumab or bevacizumab.…”
Section: -11mentioning
confidence: 99%
See 3 more Smart Citations